2019
DOI: 10.1088/1742-6596/1249/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Video Processing Techniques for the Contactless Investigation of Large Oscillations

Abstract: The experimental acquisition of large vibrations presents various technical difficulties. Especially in the case of geometric nonlinearities, dealing with very flexible, very light structures causes minimal variations in mass or stiffness to affect severely the dynamical response. Thus, sensors’ added masses change the behaviour of the structure with respect to the unloaded condition. Moreover, the most common tools regularly employed for acquisition in vibration analysis - that is to say, laser vibrometers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The second case study concerns the spar of a prototype wing, the linear and nonlinear dynamics of which have been investigated in recent studies [61,62]. Importantly, the prototype skin is supposed to completely transfer the aerodynamic loads to the spar, making the structural behaviour of the latter a good approximation of the dynamical response of the whole spar-skin ensemble.…”
Section: High Aspect Ratio Flexible Wingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second case study concerns the spar of a prototype wing, the linear and nonlinear dynamics of which have been investigated in recent studies [61,62]. Importantly, the prototype skin is supposed to completely transfer the aerodynamic loads to the spar, making the structural behaviour of the latter a good approximation of the dynamical response of the whole spar-skin ensemble.…”
Section: High Aspect Ratio Flexible Wingmentioning
confidence: 99%
“…Therefore, this value has been set as the new cut-off frequency. The centre frequencies for MO-MMFCCs were defined from the modal analysis of the wing spar and benchmarked and validated against experimental data obtained in [61,62]; they correspond, in order of increasing natural frequency, to the 1st, 2nd, 3rd, and 4th flapwise bending mode; the 1st torsional mode; the 5th flapwise flexural; the 1st chordwise bending mode; the 2nd torsional; and, the 6th flexing modes. The tenth mode (the 7th flapwise) fell over the maximum investigable frequency at 333.88 Hz and was therefore replaced by adding '1 to the begin of the array, thus resulting in To conclude, the low frequency range of LO-MMFCCs was not changed and it remains defined between 0 and f s /2, which here becomes 128 Hz.…”
Section: High Aspect Ratio Flexible Wingmentioning
confidence: 99%
“…Other non-contact alternatives exist: laser scanning is the main competitor of video-based techniques. A complete discussion will be too long to be reported here; an exhaustive comparison can be found in [14] and some related studies recently made by the Authors are reported in [15]. For the aim of this work, it is enough to say that high-speed cameras are much more common and easy to access than multi-point laser scanners, especially for untrained labourers.…”
Section: Introductionmentioning
confidence: 98%
“…This has been proven here and in previous studies to not affect the quality of measured accelerations, while being minimally invasive. Other specifications about the Raspberry PI ® IMUs utilised for the air wing spar here investigated are reported in [69]; for completeness’ sake, the most relevant technical details about them and the rest of the instrumentation are reported in Table 2.…”
Section: Methodsmentioning
confidence: 99%